Physical, Chemical and CTD (Conductivity/Temperature/Depth) Data from the Marathon II Expedition. - Martin, Margie; Talley, Lynne D; De Szoeke, Roland A (1987)
Hydrographic and CTD measurements were taken from ninety-eight stations between Honolulu, Hawaii and Kodiak, Alaska, from 4 May to 4 June 1984 on the second leg of the Marathon Expedition. This report consists of the cruise track, vertical sections, listings of all discrete hydrographic data, a subsample of the CTD data, plots of temperature and salinity as a function of pressure and plots of potential temperature as a function of salinity. Keywords:Electrical conductivity, Sea water temperature, Physical oceanography, Density, Oceanographic data, CTD measurements, Northeastern Pacific Ocean.